Assessing Gains in Science Teaching Self-Efficacy After Completing an Inquiry-Based Earth Science Course. Issue 1 (14th March 2017) - Gray, Kyle
ABSTRACT: Preservice elementary teachers are often required to take an Earth Science content course as part of their teacher education program but typically enter the course with little knowledge of key Earth Science concepts and are uncertain in their ability to teach science. This study investigated whether completing an inquiry-based Earth Science course for preservice elementary teachers improved their self-efficacy beliefs toward science teaching using the Science Teaching Efficacy Belief Instrument (STEBI-B). The results were compared against the number of years the students had been undergraduates. All students improved their science teaching self-efficacy (including the freshmen) but only the juniors and seniors experienced significant gains in outcome expectancy. The observed gains in self-efficacy were likely due to increases in cognitive content mastery—the process of successfully learning new material, and the gain in outcome expectancy were probably influenced by the number of field experiences within their teacher-education program. Geoscience departments should, therefore, offer inquiry-based Earth Science content courses designed specifically for preservice elementary teachers to improve their self-efficacy and content knowledge, thus, meeting the needs of this critical student population.